Mobilizing Krishna's world : the writings of Prince Sāvant Singh of Kishangarh - Pauwels, Heidi Rika Maria (Seattle : University of Washington Press, 2017)
Savant Singh (1694-1764), the Rajput prince of Kishangarh-Rupnagar, is famous for commissioning beautiful works of miniature painting and composing devotional (bhakti) poetry to Krishna under the nom de plume Nagaridas. After his throne was usurped by his younger brother, while Savant Singh was on the road seeking military alliances to regain his kingdom, he composed an autobiographical pilgrimage account, "The Pilgrim's Bliss" (Tirthananda); a hagiographic anthology, "Garland of Anecdotes about Songs" (Pad-Prasang-mala); and a reworking of the story of Rama, "Garland of Rama's Story" (Ram-Carit-Mala). Through an examination of Savant Singh's life and works, Heidi Pauwels explores the circulation of ideas and culture in the sixteenth through eighteenth centuries in north India, revealing how Singh mobilized soldiers but also used myths, songs, and stories about saints in order to cope with his personal and political crisis. Mobilizing Krishna's World allows us a peek behind the dreamlike paintings and refined poetry to glimpse a world of intrigue involving political and religious reform movements.
Frontmatter -- Contents -- Acknowledgments -- Notes on Texts, Transliterations, and Dates -- Introduction: Rādhā-Krishna Devotion in Kishangarh -- 1 Soldiers Marching: Kishangarh at the Crossroads -- 2 Gods and Saints Relocated: Sectarian Rivalries and Hinduism in the Making -- 3 Devotees on the Move: The Pilgrim's Bliss -- 4 Legends Mobilized: Garland of Stories and Songs -- 5 Myth Retold: Garland of Rāma's Romance -- Conclusion: Pilgrimage, Hagiography, and Scripture -- Notes -- Bibliography -- Illustrations -- Index
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Nāgarīdāsa, -- 1699-1764.; Nāgarīdāsa, -- 1699-1764.; Nāgarīdāsa, -- 1699-1764; Hindi literature -- History and criticism; Literature and society -- India, North -- History; Littérature hindi -- Histoire et critique; Littérature et société -- Inde (Nord) -- Histoire; LITERARY CRITICISM -- Asian -- Indic; HISTORY -- Asia -- India & South Asia; Hindi literature; Literature and society; North India; Ressources Internet; Criticism, interpretation, etc; History